Detection of multiple etiologies and comparison and investigation of pathological changes in small and large intestine lesions of dogs - Ozgur Kanat; Mustafa Ortatatli (Eurasian Journal of Veterinary Sciences)
Aim: This study was conducted for the purposes of investigating pathological changes in intestines of dogs, detecting prevalence of them and determining their role in being the cause of death. Materials and Methods: The intestines of 100 dead stray dogs were examined in macroscopic, histopathologic, microbiologic, and parasitic aspects. Immunohistochemical stainings were also performed for parvovirus and distemper diseases. Results: Hemorrhages in 61, ulcers in 8, parasites in 36, invagination in 14 and foreign objects in 2 of dogs were determined. Microscopically, histopathological findings such as degeneration, necrosis and desquamation in epithelium, bacteria colonies, hyperaemia, hemorrhages, fibrosis and inflammatory cell infiltrations in propria, degeneration, dilatation and hyperplasia in crypts, and depletion in lymphoid tissues were observed and their severity were scored. Canine parvovirus positive IHC reaction was found in 90 out of 100 dogs and canine distemper virus positive reaction was found in 27 dogs, also. Microbiologically, Campylobacter spp., Escherichia coli, Enterococcus spp., Streptococcus spp. are found in 58 dogs. Histopathologically, 29 acute, 51 chronic, 15 lymphocytic and plasmacytic enteritis; 5 acute, 10 chronic, 6 diffuse and 20 idiopathic mucosal colitis were diagnosed,respectively. Conclusion: It has been emphasized that alimentary tract diseases and lesions, mainly Parvoviral enteritis, are the first-degree cause of death in street dogs gathered in shelters. Generally, mixed infections were found, and it has been noticed that the lesions are increased, or primary lesions are masked according to participation period of secondary factors to infection.